Diverse Trajectories of Hikikomori Symptoms During Job Search and the Role of Identity Distress: Three Wave Longitudinal Research - Hihara, Shogo; Kambara, Kohei; Umemura, Tomotaka; Handa, Kyonosuke; Sugimura, Kazumi (Frontiers in Psychiatry, 2022)
Objective: Hikikomori, a prolonged form of social withdrawal, has received attention in various research areas. This longitudinal study aimed to identify diverse trajectories of hikikomori symptoms among young Japanese adults engaged in a job search. It also tested whether identity distress, a critical developmental issue, predicts these trajectories while controlling for other risk factors (depressive symptoms, life satisfaction, career expectations, and gender). Methods: A total of 756 third-year Japanese university students (at Time 1, Mage = 20.88 years; women: 78.97%) who engaged in job search participated in our three-wave longitudinal survey at six-month intervals. To assess hikikomori symptoms, we used the 25-item Hikikomori Questionnaire. In addition, identity distress was measured using the 10-item Identity Distress Survey. Results: Latent class growth analysis revealed four different trajectories of hikikomori symptoms. Most young adults showed severe levels and escalating hikikomori symptoms over time. In contrast, a small proportion of young adults prevented hikikomori symptoms through the period of job search. Additionally, young adults with more severe levels of identity distress followed trajectories marked by severe hikikomori symptoms after controlling for other risk factors. Conclusion: The present study’s findings contribute to developing a primary intervention for hikikomori symptoms by identifying the period of greatest risk. Group-based counseling support for hikikomori from the perspective of identity is recommended.